Antioxidant activitiy of Lactobacillus plantarum , Lactobacillus sake and Lactobacillus curvatus strains isolated from fermented Turkish Sucuk - DÜZ,MÜRÜVVET (2020)
Abstract In recent years, it is very important to find more safe and natural antioxidants than biological sources to replace synthetic antioxidants. The antioxidant properties of 22 lactic acid bacteria were investigated in vitro in the present study. The conducted in vitro antioxidant assays included scavenging the 2,2-diphenyl-1-picrylhydrazil (DPPH) free radical, metal (Fe+2) ion chelation, hydroxyl radical and superoxide radical scavenging properties, and anti-lipid peroxidation. Analysis of DPPH free radical scavenging property of microorganisms demonstrated that Lactobacillus plantarum IH14L (90.34 ± 0.40%) strain exhibited the highest activity. The highest Fe+2 chelation activity was observed with Lactobacillus curvatus GH5L (75.98 ± 5.35%), while the lowest chelation activity was observed with L. plantarum IH14L (19.80 ± 0,05). The highest and lowest hydroxyl radical scavenging strains were L. plantarum IH16L (82.25 ± 1.60%) and L. plantarum IH26L (35.60 ± 4.50) strains, respectively. Comparison of superoxide radical scavenging activities of the microorganisms demonstrated that these activities ranged between 21.63 ± 1.32% and 7.22 ± 0.04%. A positive correlation was identified between the hydroxyl radical scavenging activity of the microorganisms and the anti-lipid peroxidation property. It was found that they had the potential for use in nutritional and probiotic applications as protective and natural antioxidants.